2015
DOI: 10.1073/pnas.1501077112
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein LIN28B regulates developmental timing in the mammalian cochlea

Abstract: Proper tissue development requires strict coordination of proliferation, growth, and differentiation. Strict coordination is particularly important for the auditory sensory epithelium, where deviations from the normal spatial and temporal pattern of auditory progenitor cell (prosensory cell) proliferation and differentiation result in abnormal cellular organization and, thus, auditory dysfunction. The molecular mechanisms involved in the timing and coordination of auditory prosensory proliferation and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 83 publications
6
70
1
Order By: Relevance
“…Other mechanisms for the control of let-7a that operate at the level of DGCR8/Drosha processing have also been suggested (Piskounova et al 2008). Additionally, close homolog Lin28b also controls let-7 levels in vivo (Shyh-Chang and Daley 2013;Golden et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Other mechanisms for the control of let-7a that operate at the level of DGCR8/Drosha processing have also been suggested (Piskounova et al 2008). Additionally, close homolog Lin28b also controls let-7 levels in vivo (Shyh-Chang and Daley 2013;Golden et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…2B). In addition to Pou4f3, Lin28b is an Atoh1 target that, when overexpressed, can itself induce HC formation in explant culture (Golden et al, 2015). The overexpression of Sox4/11 can similarly convert SCs to HC-like cells in utricle explants, whereas their activity in the cochlea is unknown (Gnedeva et al, 2015).…”
Section: Recent Progress In Hc Regeneration In Mammalian Cochleaementioning
confidence: 99%
“…Further studies identified the specific miRNAs and their downstream targets. In these studies, the miRNA 183 family, miRNA 124, miRNA 210, and let7 were shown to play essential roles in HC formation during inner ear development (Golden et al, 2015; Huyghe et al, 2015; Li et al, 2010; Weston et al, 2011). The miRNA 183 family also facilitates Atoh1-promoted HC regeneration in vitro (Ebeid et al, 2016).…”
Section: Differences Between Hc Regeneration and Hc Developmentmentioning
confidence: 99%
“…In turn, LIN28 RBPs bind let-7 primary and precursor transcript and interfere with their processing by Drosha and Dicer1 (reviewed in [123]). In the developing inner ear, Lin28b is selectively expressed in pro-sensory cells, whereas let-7 miRNAs are expressed in terminally differentiated cells including hair cells and supporting cells [124]. Using inducible LIN28B and let-7g transgenic mouse lines the authors found that higher than normal levels of let-7 miRNAs resulted in premature pro-sensory cell cycle exit, whereas lower than normal let-7 levels, due to LIN28B overexpression delayed pro-sensory cell cycle exit [124].…”
Section: Role Of Epigenetic Factors and Mirnas In Inner Ear Develomentioning
confidence: 99%
“…In the developing inner ear, Lin28b is selectively expressed in pro-sensory cells, whereas let-7 miRNAs are expressed in terminally differentiated cells including hair cells and supporting cells [124]. Using inducible LIN28B and let-7g transgenic mouse lines the authors found that higher than normal levels of let-7 miRNAs resulted in premature pro-sensory cell cycle exit, whereas lower than normal let-7 levels, due to LIN28B overexpression delayed pro-sensory cell cycle exit [124]. LIN28B overexpression led to an increase in cochlear N-Myc (Mycn) and cyclin D1 (Ccnd1) expression.…”
Section: Role Of Epigenetic Factors and Mirnas In Inner Ear Develomentioning
confidence: 99%